Edukasi dan Pemanfaatan Fintech (Aplikasi Wallet) Dalam Pengelolaan Keuangan Pada Usaha UMKM Hot Geprek Jaja_nandiana - Susanti, Neri; Delpania, Delpania; Asmarita, Deva; Maynaki, Nexy (Universitas Dehasen Bengkulu, 2022)
The business that is currently in our spotlight is the MSME Hot Geprek Jaja_nandiana business. Where the Hot Geprek business is still using the Financial Statements manually which is irregular so that the owner of Hot Geprek Jaja_nandiana has difficulty knowing his monthly income and expenses. Based on these problems, we aim to help business owners by providing education and training on the use of fintech (financial technology) in financial management. Financial management that utilizes fintech will be much faster, and provide convenience, as well as accuracy. The methods used in this training are: identification, preparation, implementation, and evaluation. The results of this activity showed positive results in understanding the use and utilization of fintech applications in financial management and being able to apply them to their MSME businesses.